FROM COMPLIANCE TO CHARACTER: EVALUATING THE EFFECTIVENESS OF SCHOOL-WIDE DISCIPLINE ON STUDENT BEHAVIOR (Contemporary Journal of Social Science Review, 2025)
This study examines the effectiveness of school discipline practices at the secondary school level and their effect on students' behavior. The research was of a descriptive survey type in which 200 respondents (secondary and higher secondary school principals and teachers) were drawn from 50 government schools out of 100 of each tehsil randomly selected from the District selected based on the theoretical framework of assertive discipline (Canter, 1984) and reality therapy (Glasser, 1969). A structured questionnaire was used to collect data and subsequently analyzed using descriptive statistics, Pearson correlation and regression analysis in SPSS 25. Six constructs of discipline: general discipline, assembly practices, school discipline, class discipline, school environment, and rules and regulations, and how they collectively affect student behavior, were studied. The findings showed that discipline, class discipline, and school discipline had statistically significant positive regression coefficients on student behavior (p < .05), while the other factors (assembly, environment, rules and regulations) showed positive regression but were not statistically significant (p > .05). The elements of proactivity (such as morning assemblies, classroom management, and rules) were identified as practices that foster responsibility, concentration, and positive attitudes toward school. When combined with relational and strengths-based practices, reactive interventions such as "disciplinary" committees and consequence-based explanations of misbehavior were effective in promoting behavioral correction. The results highlight the importance of investing in proactive as well as reactive discipline approaches in the school environments, which ensure safe and orderly learning spaces and foster inclusive learning environments for students' holistic behavioural development in Pakistan.